A new nematode, Dichelyne alatae sp. n. (Cucullanidae), from Sillaginopsis panijus (Pisces) of West Bengal, India - De, N C; Maity, R N (Folia parasitologica, 1995)
A new nemarode, Dichelyne alatae sp. n., is described on the basis of the worms recovered from the intestine of the whiting, Sillaginopsis panijus (Perciformes: Sillaginidae) from the estuary of the river Hooghly at Kalyani, West Bengal, India. Dichelyne alatae differs from congeners in having a small body size, deirids posterior to the oesophagus, short and wide caudal alae at the level of cloacal opening, unequal, alate spicules, a shield-shaped gubernaculum, a different number of caudal papillae and a conical tail with spines in its distal region.
Keywords: Nematoda; Indie; hlístice; Animals; mužské pohlaví; ženské pohlaví; Perciformes; zvířata; Female; Intestines; India; Male; střeva